Аналітичні дослідження контактного руху легких домішок у пневмосепаруючому каналі - Нестеренко, О. В.; Петренко, Д. І.; Павленко, І. І.; Лещенко, С. М.; Гончарова, С. Я.; Nesterenko, О.; Petrenko, D.; Pavlenko, I.; Leschenko, S.; Honcharova, S. (ЦНТУ, 2017)
Враховуючи складність та випадковість пневмосепараційного процесу, на який впливає значна кількість факторів, є необхідним вирішення наукового завдання щодо встановлення закономірностей контактної взаємодії легких домішок з зерном в зоні пневмосепарації. В статті розглянуто контактний рух легких домішок через багатошаровий зерновий потік в вертикальному пневмосепаруючому каналі (ПСК) при їх багаторівневому одношаровому введенні. Отримані теоретичні залежності, які дозволяють встановити закономірності впливу основних конструктивно-технологічних параметрів ПСК на якість процесу сепарації. The separation of grain materials in the air separation channel occurs in rather difficult conditions, since light impurities, which are located in the lower cereal layers for the separation into the sediment chamber, require, with a minimum change in trajectory, to cross all above-placed seed moving in a downward direction. As a result of this movement there is a contact between light impurities and grain, which significantly affects the quality of cleaning. Therefore, a very important task is the analytical research aimed at investigating the contact interaction of light impurities with grain in the air separation channel and its effect on the quality of separation. Taking into account the multilevel feeding of the material in the PSC it is necessary to determine its influence on the qualitative parameters of the separation process and the establishment of the basic laws of the interaction of light impurities with grain material in the working area of the PSC. As a result of the theoretical analysis, the regularity of the contact motion of light impurities is established at the multilevel feeding of grain material in the PSC, which allows to obtain the averaged trajectories of impurities after interaction with grain layers during aerodynamic separation. It is determined that the allocation of light impurities depends on their time and velocity through the grain layers, which vary depending on the angle of contact of impurities with grain, as well as from the place of installation of the upper point of the output of grain hɠ.ɜ.. With six-level introduction of the material with the placement of grain particles in the direction of movement in the PSC with an interval equal to their size (2R) the place of installation of the upper point of the output of grain hɠ.ɜ. must be at a height hɠ.ɜ.= 0,05 ... 0,055 m relative to the level I of the input. The purpose of further researches should be to determine the qualitative characteristics of pneumatic separation in the contact interaction of grain material with air flow at its multilevel introduction into the PSC.
Analytical research the contact interaction of light impurities in the pneumatic separating channel
Keywords: пневмосепарація; повітряний потік; багаторівневе введення; зерновий матеріал; пневмосепаруючий канал (ПСК); введення зерна; контактний рух легких домішок; pneumatic separation; air velocity; multilevel feeding; grain material; pneumatic and separating channel (PSC); contact motion of light impurities